2009
DOI: 10.26719/2009.15.4.1005
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of acute poisoning in Al-Qassim region: a surveillance report from Saudi Arabia, 1999-2003

Abstract: We reviewed all registered cases of acute chemical poisoning reporting to the preventive medicine department in the Qassim Region of Saudi Arabia from 1999 to 2003. The number of cases increased from 66 to 114 during the study period. Mean age of patients was 17.7 years, and over 39% were children aged ≤ 5 years. Pesticides were the most common chemical involved; paracetamol and other analgesics were also frequently reported. The oral route was the most frequent, while vomiting was the commonest symptom. Nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
62
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 9 publications
14
62
1
Order By: Relevance
“…It also may be due the economic growth of the country and the associated increased availability of different agrochemicals in the country. This study showed an increase in cases from9 to 46.6%between the years2011 to 2014 an observation that is in agreement with other studies (Moazzam et al 2009). When the data was analyzed by month, July was found to have the greatest number of admitted patients (14.6%).This is likely because it is the month when the most chemicals are used by farmers to increase their crop yield.An apparent decrease in the number of the patients was observed in March (2.6%), which is likely due to seasonal variation.…”
Section: Discussionsupporting
confidence: 82%
“…It also may be due the economic growth of the country and the associated increased availability of different agrochemicals in the country. This study showed an increase in cases from9 to 46.6%between the years2011 to 2014 an observation that is in agreement with other studies (Moazzam et al 2009). When the data was analyzed by month, July was found to have the greatest number of admitted patients (14.6%).This is likely because it is the month when the most chemicals are used by farmers to increase their crop yield.An apparent decrease in the number of the patients was observed in March (2.6%), which is likely due to seasonal variation.…”
Section: Discussionsupporting
confidence: 82%
“…This may result from easily accessible places of poisons and attractive color or container of the poison for the child. Other studies matched the same result[16] [17]. Most of the studied…”
supporting
confidence: 80%
“…[3] Advances in technology and social development have resulted in the availability of most drugs and chemical substances in the community. [4,5] Household chemical agents and prescribed drugs are the most common poisoning agents in developed world, but agro-chemicals are the most common poisoning agents in developing countries. [6] The pesticides used for agricultural purposes are easily available in the market and poisoning with such products are more commonly noticed in rural area where people largely depend on agriculture for their living.…”
Section: Introductionmentioning
confidence: 99%